Determining the Quality of Laying Parent Duck Seeds Using the SAW Method - Wati, Widya; Yusfrizal, Yusfrizal; Simanjutak, Magdalena (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The selection of laying ducks on a farm is an important step for the continuity of activities in it. Increasing the selection of laying ducks requires quality standards to measure its success. This increase uses a simple additive weighting (saw) method in a decision support system. The increase in the selection of laying ducks is based on several criteria that have been applied, including the age of the ducks, the weight of the ducks, the shape of the duck feathers, and the shape of the duck wings. The results of this study indicate that the proposed model can be used properly in carrying out the selection of parent ducks for laying eggs. The SAW method is able to produce decisions in the form of the best alternative that can be used to assist decision makers. so that it can assist in the selection of broodstock ducks in an ordinary or intensive farm.